Dieta Neandertalczyka- problem wielu nauk - Woyciechowski, Jędrzej (2023)
As one of the most important conditions for the existence of living beings, food acquisition is reflected in every sphere of their life. When trying to learn about the diet of the Neanderthal – an extinct hominin, one cannot limit one self to only one scientific discipline. This work, based on the latest discoveries of archaeology, palaeontology, anthropology and ethnography, shows the issue of the Neanderthal diet in a multidisciplinary approach. The author tries to prove that this is the optimal way to present this issue.
Keywords: diet; Neanderthal; multidisciplinary research